2015
DOI: 10.1513/annalsats.201406-254mg
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stromal Cells for Acute Respiratory Distress Syndrome

Abstract: Based on preclinical data, cell-based therapy with bone marrowderived mesenchymal stem (stromal) cells (MSCs) is a potentially attractive new therapeutic option for treating patients with the acute respiratory distress syndrome. Small and large animal models of acute lung injury from endotoxin, live bacteria, and sepsis have shown that MSCs can decrease lung injury and increase survival. The mechanisms for benefit are mediated in part by paracrine release of several antiinflammatory cytokines, keratinocyte gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…MSCs have the ability to release multiple soluble factors, such as growth factors, antiinflammatory cytokines, and antimicrobial peptides, which can improve endothelial and epithelial permeability, modulate innate and adaptive immunity, and protect against oxidative damage-induced apoptosis [50]. In our present study, we also found that the stem cells had a protective effect on endothelial cells, in line with previous reports [12,17,18,20,51]. Because the indirect co-culture system was adopted during our experiment, we think that the immunomodulatory effect of MSCs on inflammation and oxidative stress can be ascribed to a paracrine mechanism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MSCs have the ability to release multiple soluble factors, such as growth factors, antiinflammatory cytokines, and antimicrobial peptides, which can improve endothelial and epithelial permeability, modulate innate and adaptive immunity, and protect against oxidative damage-induced apoptosis [50]. In our present study, we also found that the stem cells had a protective effect on endothelial cells, in line with previous reports [12,17,18,20,51]. Because the indirect co-culture system was adopted during our experiment, we think that the immunomodulatory effect of MSCs on inflammation and oxidative stress can be ascribed to a paracrine mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…As we found that the cell growth curve of MSCs was similar to that of MSCs-HO-1 it suggests that the additional protective effect of MSCs-HO-1 was not associated with cell viability. Accumulating evidence using different preclinical animal models, including endotoxin-induced, live bacteria-induced, sepsis-associated, and pancreatitis-associated lung injury, has shown that cell-based therapy with MSCs is a potentially attractive option for treating ALI/ARDS [18]. The mechanisms of MSC protection against ALI/ARDS include multilineage differentiation potential (e.g., cell replacement and tissue regeneration), paracrine (e.g., secretion of antimicrobial and repair factors), and cell-cell contactdependent (e.g., transfer of nucleic acids and organelles) mechanisms [17].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have potential in tissue regeneration because of their anti-inflammatory and immunosuppressive properties [93]. To date, there have been many extensive studies and clinical trials examining the use of MSC-based therapy as a regenerative tool in many clinical disorders, including lung tissue repair and regeneration after acute respiratory distress syndrome (ARDS) [94]. The repair mechanisms are partly mediated by the paracrine secretion of cytokines and growth factors by MSCs, and in many cases these paracrine factors are packaged within EVs.…”
Section: Reviewmentioning
confidence: 99%
“…W-peptide (chemoattractant) was Of note, the extent of mitochondrial dysfunction in the lungs has been shown to correlate with mortality in sepsis (19,20). Approaches to prevent mitochondrial dysfunction or to restore mitochondrial bioenergetics may diminish the severity of sepsis-associated lung injury (21)(22)(23).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%